Career Incentives, Performance Base Pay, Organizational Benefits Influencing Employee Performance: A Case on Libyan Tobacco Company - Omaro, Wafa Yosef (2011)
This study discusses all the antecedents which influence employee performance in Libyan Tobacco Company Tripoli. The antecedents which are used in this study are career incentive; performance based pay and organizational benefits. This study has distributed 250 questionnaires among the Libyan Tobacco company. The questionnaire return was 200 and among them 158 were valid questionnaire, which are used in the analysis. Employee performance in Tobacco Company at Tripoli of Libya defined by the underpinning expectancy theory which is predicated on a belief that individuals will exert effort if they expect it will result in an outcome they value. However, reinforcement theory also posits a direct relationship between a desired target behavior such as performance and its consequences such as pay. The aim of this research is to investigate the influence of career incentives; performance based pay and organizational benefits influencing employee performance in Libyan Tobacco Company. This study has hypothesized that there is a positive relationship of career incentives; performance based pay and organizational benefits with employee performance. The research has been conducted in Libyan Tobacco Company in Tripoli and the questionnaire was distributed among the employees in Libyan Tobacco Company. The study has used frequency, factor analysis, reliability, correlations and regression analysis to analyze the data. The findings have indicated that performance base pay is the best predictor of employee performance.